+0

# How do you derive the power rule that is used in calculus for differentiation?

0
502
2

How do you derive the power rule that is used in calculus for differentiation?

Guest Oct 1, 2014

#2
+92673
+5

We can also find this by using the difference quotient and the binomial theorem......suppose we want to find the derivative of xn   ...... so we have.....

lim          [ (x + Δx)n - xn ] / (Δx)   Δx → 0

And by the binomial theorem, we can write

lim          [ xn + C(n, 1)xn-1 Δx + C(n,2) xn-2 Δx2 + ..... +C(n, n-1) xΔxn-1 + C(n, n)Δxn  - xn ] / (Δx)

Δx → 0

lim          [C(n,1) xn-1 Δx + C(n,2)xn-2 Δx2 + ..... +C(n, n-1) xΔxn-1 +C(n, n) Δxn ] / (Δx)

Δx → 0

.... factor out Δx in the numerator...

lim         (Δx) [C(n, 1) xn-1  +C(n, 2) xn-2 Δx + ..... +C(n, n-1) xΔxn-2 +C (n, n) Δxn-1 ] / (Δx)

Δx → 0

lim          [C(n, 1) xn-1  + C(n, 2) xn-2 Δx + ..... +C(n, n-1) xΔxn-2 + C(n, n) Δxn-1 ]

Δx → 0

And taking the limit as Δx → 0 we have

C(n,1) x n-1   ..........  but   C(n, 1) is just n......so we have......

nxn-1

CPhill  Oct 1, 2014
#1
+17746
+5

Start by writing  x^n as e^(n lnx ).

d( x^n )/dx  =  d( e^(n lnx ) )/dx

=  e^( n ln x ) · d( n ln x )/dx                        chain rule

= x^n · ( n/x )

= n · x^( n - 1 )

geno3141  Oct 1, 2014
#2
+92673
+5

We can also find this by using the difference quotient and the binomial theorem......suppose we want to find the derivative of xn   ...... so we have.....

lim          [ (x + Δx)n - xn ] / (Δx)   Δx → 0

And by the binomial theorem, we can write

lim          [ xn + C(n, 1)xn-1 Δx + C(n,2) xn-2 Δx2 + ..... +C(n, n-1) xΔxn-1 + C(n, n)Δxn  - xn ] / (Δx)

Δx → 0

lim          [C(n,1) xn-1 Δx + C(n,2)xn-2 Δx2 + ..... +C(n, n-1) xΔxn-1 +C(n, n) Δxn ] / (Δx)

Δx → 0

.... factor out Δx in the numerator...

lim         (Δx) [C(n, 1) xn-1  +C(n, 2) xn-2 Δx + ..... +C(n, n-1) xΔxn-2 +C (n, n) Δxn-1 ] / (Δx)

Δx → 0

lim          [C(n, 1) xn-1  + C(n, 2) xn-2 Δx + ..... +C(n, n-1) xΔxn-2 + C(n, n) Δxn-1 ]

Δx → 0

And taking the limit as Δx → 0 we have

C(n,1) x n-1   ..........  but   C(n, 1) is just n......so we have......

nxn-1

CPhill  Oct 1, 2014